GENERAL OVERWIEV ON EU ECONOMY - NICOLETA GEORGETA PANAIT (Challenges of the Knowledge Society)
The impact of the international economic crisis on new EU member states has proven to be more severe than the first estimates of the economic analysts. The situation is different for each Member State, the nature and the dimension of the challenges faced are not identical, and the pace of reform is not the same. The economic crisis has prompted intense and sustained action by the EU's national governments, the European Central Bank and the Commission. All have been working closely together to support growth and employment, ensure financial stability, and put in place a better governance system for the future. Sustainable development in the future is the common responsibility of all Member States and EU institutions, because our economies are closely interlinked, and the EU economic governance now reconfigured to provide more effective responses at the policy level, to give a good reaction to the present and the future challenges.